Economic evaluation of different technologies for pasture recuperation - Filho, Antônio Viana; Balbino, Luiz Carlos; Oliveira, Itamar Pereira de; Barcellos, Alexandre de Oliveira (Pesquisa Agropecuaria Brasileira, 1999)
The aim of this study was to compare the economic viability of some technologies for recovery of degraded pastures, for a period of time, evaluating animal development under rotational grazing. The activities were conducted in Brasilândia, MS, Brazil, studying six modules of 5 ha each. Modules T1 (corn + Brachiaria brizantha), T2 (rice + B. brizantha), and T3 (rice + B. brizantha + Calopogonium mucunoides) had been renewed following the procedures recomended by the "Barreirão System". Module T4 had been formed according to traditional regional procedures, with B. brizantha. Modules T5 and T6 were selected in the vicinity of the others, to serve as controls; B. humidicola was predominant in module T5, whereas module T6 was predominantly formed by B. humidicola and B. decumbens. Economic evaluation was based on cereal production, live weight gain and stocking rate. It was observed that in modules T1, T2, T3, and T4, exploration of beef cattle grazing on recovered pastures is a profitable activity. Pasture renewal according to agricultural modules T1, T2, and T3 have advantages over the traditional models due to the cereal production which defrays the cost to recover the pastures.